2020
DOI: 10.3389/fvets.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Grape Seed Meal Bioactive Compounds on the Colonic Microbiota of Weaned Piglets With Dextran Sodium Sulfate-Induced Colitis Used as an Inflammatory Model

Abstract: Microbiota affects host health and plays an important role in dysbiosis. The study examined the effect of diet including grape seed meal (GSM) with its mixture of bioactive compounds on the large intestine microbiota and short-chain fatty acid synthesis in weaned piglets treated with dextran sodium sulfate (DSS) as a model for inflammatory bowel diseases. Twenty-two piglets were included in four experimental groups based on their diet: control, DSS (1 g/kg/b.w.+control diet), GSM (8% grape seed meal inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 78 publications
0
10
0
1
Order By: Relevance
“…This bacterium seems to be favoured by the insertion of soybean meal in the diet of piglets [ 54 ], which might explain our results since this protein source was an important component of the diet used in the present study. The abundance of Megasphaera was numerically lower in the cecum of piglets receiving ZnO only, but the role of these commensal bacteria in the swine intestines deserves better attention [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium seems to be favoured by the insertion of soybean meal in the diet of piglets [ 54 ], which might explain our results since this protein source was an important component of the diet used in the present study. The abundance of Megasphaera was numerically lower in the cecum of piglets receiving ZnO only, but the role of these commensal bacteria in the swine intestines deserves better attention [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that the diet with 8% whole grape seed meal (GSM), containing high amounts of polyphenols, PUFAs and fiber, was efficient in counteracting DSS-induced colon inflammation by reducing pro-inflammatory cytokines and chemokines production and by attenuating mitogen-activated kinases (MAPKs) and nuclear factor kappa B (NF- k B) gene and protein expressions [ 28 ]. Furthermore, GSM diet positively modulated the microbiota in DSS-treated piglets, stimulating the growth of beneficial bacteria and the production of butyrate and isobutyrate short-chain fatty acids (SCFAs) [ 29 ]. We thus hypothesized that whole GSM, by its content in bioactive compounds, could improve also the epithelium integrity and functionality affected by the DSS challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Grosu et al found that in healthy pigs, the additive increased the relative abundances of Bacteroidetes, Proteobacteria, and Prevotella and decreased the relative abundances of Firmicutes, Lachnospiraceae, and Lactobacillus [ 186 ]. In pigs with DSS-induced colitis, grape seed meal intake attenuated a DSS-induced Roseburia increase while stimulating the growth of Anaerovibrio and Megasphaera and butyric acid production [ 187 ].…”
Section: Resultsmentioning
confidence: 99%